Exploring the need for formal coaching programmes: Experiences of engineering graduates in a South African mining company - Hanifa Hoosen; Nelesh Dhanpat (Acta Commercii)
Orientation: Organisations face increasing pressure to support new graduates as they transition into professional roles. Formal coaching has emerged as a key strategy to bridge the gap between academic training and workplace demands, particularly in technical industries like mining.